2010
DOI: 10.1016/j.elecom.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Thin film pyrolytic carbon electrodes: A new class of carbon electrode for electroanalytical sensing applications

Abstract: This communication describes the electrochemical properties of thin pyrolytic carbon (PyC) films created using a reliable, non-catalytic chemical vapour deposition (CVD) process. After deposition, the electron transfer characteristics of the films are optimised using a simple oxygen plasma treatment. The redox probes Fe + + are employed to demonstrate that the resulting material is endowed with a large electrochemical surface area and outstanding electron transfer properties. Atomic force microscopy (AFM), Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…28 Recently, it has been demonstrated that PyC can be modified using a simple plasma processing step which drastically improves the electrochemical activity of the material. 29 Exposing a PyC film to reactive oxygen plasma was found to expose a greater density of active edge-plane graphitic sites and crystalline defects compared to inert basal-plane sites. In addition, it is proposed that the oxygen functionalisation which results from the treatment further facilitate charge transfer processes when characterised using redox electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, it has been demonstrated that PyC can be modified using a simple plasma processing step which drastically improves the electrochemical activity of the material. 29 Exposing a PyC film to reactive oxygen plasma was found to expose a greater density of active edge-plane graphitic sites and crystalline defects compared to inert basal-plane sites. In addition, it is proposed that the oxygen functionalisation which results from the treatment further facilitate charge transfer processes when characterised using redox electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that the surface of carbon materials is prone to react spontaneously with atmospheric oxygen to form surface oxide functional groups that change its chemical nature and affect its electrochemical performances [13]. Examination of the existence of surface oxide functional groups with Fourier transform infrared (FTIR) spectroscopy [36] and X-ray photoelectron spectroscopy (XPS) method [33] indicate the presence of a low amount of carbonyl and hydroxyl functional groups on the surface of the PCF electrode.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Pyrolytic carbon films (PCFs), nanostructured forms of carbon belonging to the above groups, have been reported as new and attractive electrode materials for electroanalytical applications [33][34][35][36]. The structure is composed of two-dimensional hexagonal graphitic sheet aggregates with more or less preferential orientation to the substrate surface, depending on the chemical vapor deposition (CVD) processing conditions [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…While the electrochemistries of standard carbon electrodes like glassy carbon and carbon black have been thoroughly studied, newly developed nanoscale carbon materials present a potent new class of carbon electrodes to explore. A great deal of attention has focused on highly ordered carbon nanomaterials like graphene [1][2][3] and carbon nanotubes, 4 in addition to less ordered carbons like pyrolized graphite, 5 carbon foams 6 and fibers. 7 One approach to forming nanoscale carbon electrodes is through thin film deposition, which can produce free standing electrodes for easy incorporation into sensors, microelectronic components, and energy storage and conversion devices.…”
mentioning
confidence: 99%